Distribution of Heritage Association of Harta Pusaka Tinggi And Harta Pusaka Rendah in Padang Pariaman - Elfia, Elfia; Meirison, Meirison; Muhammadi, Qasim (Al-Ahkam, 2020)
This research is motivated by a phenomenon of the distribution of inheritance that occurs in the Nagari Lurah Ampalu community. They hand over inheritance (pusako rendah) at the pusaka tingg" property to girls. Some of the problems in this study are, the factors causing the community to divide pusaka tinggi and pusaka rendah are not based on Islamic law and the method of settlement by Shari'a for the two types of inherited assets that have been mixed. Data in this paper were obtained through interviews and documentation. The factors causing the community to share this inheritance are derived from the traditions of previous ancestors, the lack of community knowledge in faraid science and the existence of coercion between heirs. The solution used by local clerics is to calculate the price of pusaka tinggi land and the proceeds of the sale are left to the pusaka tinggi property holders. Assets that are on ancestral inheritance are distributed to heirs according to the law of farÄ'iá¸. The final solution is to move or eliminate assets above pusaka tinggi .